Reconfiguring Hell: Urgency and Salvation in the Faroe Islands. (1st December 2022) - Jensen, Jan
Abstract: This article focuses on a Pentecostal church in the Faroe Islands and the way in which members of the church relate to the concepts of life, death, Heaven and Hell. As I argue throughout, the concepts of damnation and Hell, which have historically played a central role in Evangelical churches in the country, have now started to become played down in favour of a 'Gospel of Life'. I explore this change by paying attention to the existential stakes involved in living life as a member of a Christian movement which sees it as an imperative to spread the Gospel to individuals who are not confessed Christians. This work contributes to a growing amount of literature within the anthropology of Christianity that deals with Pentecostal and charismatic Christian movements. It is my argument that while much earlier literature dealing with phenomena such as conversion and millenarianism has been presented, the question of the 'small' biographical aspects of salvation and (the after-)life have not been adequately explored. Finally, I attempt to offer up an example of how changing ontological claims affect religious practice among the people in question. Cet article se concentre sur une église pentecôtiste dans les îles Féroé et sur la manière dont les membres de l'église se rapportent aux concepts de vie, de mort, de paradis et d'enfer. Comme je le soutiens, les concepts de damnation et d'enfer, qui ont historiquement joué un rôle central dans les églises évangéliques du pays, ont maintenant commencé à être minimisés en faveur d'un "Évangile de la vie". J'explore ce changement en prêtant attention aux enjeux existentiels de la vie en tant que membre d'un mouvement chrétien qui considère comme un impératif de diffuser l'Évangile à des individus qui ne sont pas des chrétiens confessés. Ce travail contribue à une quantité croissante de littérature au sein de l'anthropologie du christianisme qui traite des mouvements chrétiens pentecôtistes et charismatiques. Je soutiens que, si de nombreux ouvrages antérieurs traitant de phénomènes tels que la conversion et le millénarisme ont été présentés, la question des "petits" aspects biographiques du salut et de l'après-vie n'a pas été suffisamment explorée. Enfin, j'essaie d'offrir un exemple de la manière dont l'évolution des revendications ontologiques affecte la pratique religieuse chez les personnes en question.